Free Medical Treatment for the Elderly in Pintu Langgit Village, Angkola Julu District, Padang Sidimpuan City in 2023 - Rya Anastasya Siregar; Novita Sari Batubara (PT Inovasi Pratama Internasional, 2022)
There is enhancement level health on public in Indonesia, caused age hope life increase so that the elderly (elderly/elderly) group is increasing in number. This life expectancy as wrong an indicator to measure the degree of public health in Indonesia. Purpose of dedication to community, namely to detect early health if there is a health problem in the community elderly age. Examination can be done according to the needs or history of the disease of the elderly. Target program devotion This is inhabitant village Pittu Langit special his elderly. Method Which used is method education public with counseling, inspection health and gift drug free on elderly. The results of community service activities in Pintu Langgit Village, Angkola Julu District Padang Sidimpuan City carried out well with 30 elderly participants. Conclusions of program devotion This that is Public and Participant Elderly follow activity This very enthusiastic in Health check-up counseling activities and the provision of free medicines were carried out well. This matter proven with enthusiastic Elderly in inspection health. After counseling This Suggested to public specifically age elderly, so that do inspection his health in facility health closest by particularly routine control pressure blood, cholesterol, sugar blood and sour tendon.